A real value negative selection algorithm based on antibody evolution for anomaly detection - Yang, Tao; Chen, Wen; Liu, Zhengjun; Lin, Ping (2018 Tenth International Conference on Advanced Computational Intelligence (ICACI), 2018)
Traditional negative selection algorithm generates immune detectors randomly, when the antigens distribute complicatedly and unevenly, the detectors are difficult to generate in the gap which between self samples and nonself samples. On the contrary, the detectors are redundant in the regions where antigens distribute sparsely. To deal with this limitation, this paper proposes a real value negative selection algorithm based on antibody evolution (AERNSA). AERNSA contains two kinds of antibody evolution: evolution based on "distribution of antigens" and evolution based on "antibody competition". The two kinds of evolution can guarantee the detectors to be effectively generated in the region where antigens distribute densely and to reduce the redundant detectors in the area where antigens distribute sparsely. The experimental results show that, on the artificial dataset Rectangle (2D) and the UCI standard datasets, compared with the classical RNSA and V-detector algorithm, AERNSA can significantly improves the detection rate with fewer detectors and shorter training times.